MBE grown germanium tunnel-junctions - Burstein-moss effect and band-edge luminescence in the Ge Zener-Emitter - Koerner, R.; Fischer, I. A.; Schwarz, Daniel; Clausen, C.; Oehme, Michael; Schulze, J. (Semiconductor Science and Technology, 2017)
We investigated the Burstein-Moss (BM) shift by electroluminescence experiments in the Ge Zener-Emitter. Due to fast transit times through a tunneling barrier (few ps), electrons can be accumulated in the indirect as well as the direct conduction band by Zener band-to-band tunneling. The resulting shift can thus be assigned to the band-filling effect in the indirect conduction band (BM shift of 39 meV) as well as the direct conduction band (BM shift of 58 meV). Theoretical modelling has been carried out and shows good agreement with our experimental data from the Zener-Emitter.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Burstein-Moss effect; germanium; integrated optical devices; silicon photonics